Effect of the nandrolone decanoate on the efficiency of spermatogenesis of sedentary rats and rats subjected to physical training - DOI: 10.4025/actascihealthsci.v32i1.5741 - Marcela Paiva Foletto; Cecília Edna Mareze da Costa; Fernanda Ferrari; Solange Marta Franzói-de-Moraes; Tânia Mara Segatelli (Acta Scientiarum. Health Sciences, 2009)
Spermatogenesis is a complex, highly organized and coordinated process that results in the production of male gametes. This process is influenced by a number of drugs that enhance physical performance, which have been used mainly by young people, athletes or not, seeking to gain athletic performance or only a prominent social position. The objective of this study was to evaluate the effects of the anabolic steroid nandrolone decanoate on the efficiency of spermatogenesis in sedentary rats and rats subjected to physical training. Twenty-four male rats were divided into four experimental groups: sedentary control, sedentary treated, trained control and trained treated. Treated animals received intramuscular injection of nandrolone decanoate (0.5 mg kg-1 body weight) during the last four weeks of physical training. The training program consisted of running on a programmable ergometer treadmill, tailored to train eight rats simultaneously, for nine weeks. We evaluated the morphological and morphoquantitative profiles of the male reproductive system. The results showed that the treatment causes a reduction in the efficiency of spermatogenesis; however, when associated with physical training, this compensates for the anabolic action, keeping the process of spermatogenesis within normality.